MICROTUBULE BIOGENESIS AND CELL SHAPE IN OCHROMONAS : III. Effects of the Herbicidal Mitotic Inhibitor Isopropyl N-Phenylcarbamate on Shape and Flagellum Regeneration - Brown, David L. (The Rockefeller University Press, 1974)
The role of microtubules and microtubule nucleating sites in the unicell, Ochromonas has been examined through the use of two mitotic inhibitors, isopropyl N-phenylcarbamate (IPC) and isopropyl N-3-chlorophenyl carbamate (CIPC). Although IPC and CIPC have little or no effect on intact microtubules, the assembly of three separate sets of microtubules in Ochromonas has been found to be differentially affected by IPC and CIPC. The assembly of flagellar microtubules after mechanical deflagellation is partially inhibited; the reassembly of rhizoplast microtubules after pressure depolymerization is totally inhibited (however, macrotubules may form at the sites of microtubule initiation or elsewhere); and, the reassembly of the beak set of microtubules after pressure depolymerization may be unaffected although similar concentrations of IPC and CICP completely inhibit microtubule regeneration on the rhizoplast. These effects on microtubule assembly, either inhibitory or macrotubule inducing, are fully reversible. The kinetics of inhibition and reversal are found to be generally similar for both flagellar and cell shape regeneration. Incorporation data suggest that neither IPC nor CIPC has significant effects on protein synthesis in short term experiments. Conversely, inhibiting protein synthesis with cycloheximide has little effect on microtubule regeneration when IPC or CIPC is removed. Although the exact target for IPC and CIPC action remains uncertain, the available evidence suggests that the microtubule protein pool or the microtubule nucleating sites are specifically and reversibly affected. Comparative experiments using the mitotic inhibitor colchicine indicate some similarities and differences in its mode of action with respect to that of IPC and CIPC on assembly and disassembly of microtubules in these cells.